Pengaruh Jumlah Anggota, Size, Likuiditas, dan Rentabilitas Koperasi terhadap Permintaan Jasa Audit Eksternal - Fikri Rizki Utama (Universitas Islam Sultan Agung (UNISSULA), Faculty of Economics, Department of Accounting, 2019)
The purpose of this research is to empirically examine the influence of the number of members of the cooperative, size, liquidity, and rentability of cooperatives to demand external audit services. This study uses a sample of Cooperative Employees (Kopkar) in the city of Bandar Lampung during 2009-2011 using purposive sampling method. The analysis in this study uses logistic regression equation. The result of this study found that the size variable has a significant influence on the demand for external audit services. While the variable of a number of cooperative members, liquidity, and rentability do not significantly influence the demand for external audit services.Keywords: Request for External Audit Services, Cooperative of Employees, Number of cooperative members, Size, Liquidity, and Rentability.